2004
DOI: 10.1038/oby.2004.9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Overweight and Academic Performance: National Study of Kindergartners and First‐Graders

Abstract: DATAR, ASHLESHA, ROLAND STURM, AND JENNIFER L. MAGNABOSCO. Childhood overweight and academic performance: national study of kindergartners and first-graders. Obes Res. 2004;12:58 -68. Objective: To examine the association between children's overweight status in kindergarten and their academic achievement in kindergarten and first grade. Research Methods and Procedures:The data analyzed consisted of 11,192 first time kindergartners from the Early Childhood Longitudinal Study, a nationally representative sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
261
6
24

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(319 citation statements)
references
References 45 publications
28
261
6
24
Order By: Relevance
“…Although not a direct measure of intelligence, in one further prospective study school learning difficulties and poor performance in school exams were associated with a greater risk of being obese in young adulthood. 12 Three other prospective studies found that being overweight or obese in early childhood was associated with poor performance in school tests and assignments later in childhood, [13][14][15] though in one of these studies the association was attenuated to the null with adjustment for parental socioeconomic position. 13 In the Danish Military Survey the association between early life intelligence and later obesity attenuated to the null with adjustment for educational attainment and the authors concluded that education mediated the association between childhood intelligence and adult obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not a direct measure of intelligence, in one further prospective study school learning difficulties and poor performance in school exams were associated with a greater risk of being obese in young adulthood. 12 Three other prospective studies found that being overweight or obese in early childhood was associated with poor performance in school tests and assignments later in childhood, [13][14][15] though in one of these studies the association was attenuated to the null with adjustment for parental socioeconomic position. 13 In the Danish Military Survey the association between early life intelligence and later obesity attenuated to the null with adjustment for educational attainment and the authors concluded that education mediated the association between childhood intelligence and adult obesity.…”
Section: Introductionmentioning
confidence: 99%
“…12 Three other prospective studies found that being overweight or obese in early childhood was associated with poor performance in school tests and assignments later in childhood, [13][14][15] though in one of these studies the association was attenuated to the null with adjustment for parental socioeconomic position. 13 In the Danish Military Survey the association between early life intelligence and later obesity attenuated to the null with adjustment for educational attainment and the authors concluded that education mediated the association between childhood intelligence and adult obesity. 9 In addition to being affected by intelligence, educational attainment is also influenced by biological factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These chronic health conditions increase with time and are higher among males (Van Cleave et al, 2010). In addition, obese children as adults are also prone to psychological problems such as low selfesteem and depression (Sanchez-Villegas et al, 2010), while academic achievements of obese preschool and first grade children are lower (Datar et al, 2004;Taras and Potts-Datema, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These results support findings from previous studies that looked into the effect of BMI on academic performance and verified that normal weight students showed better grades, better trends in reading scores, greater school attendance and better discipline when compared with overweight 2 and underweight 5 counterparts. Furthermore, children who were overweight from kindergarten to the end of 3 rd grade showed poor academic achievements and more behavioral problems 1 . However, no study has examined the association of both underweight and overweight and academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-known deleterious effects of overweight on physical health, some studies have reported the association between high Body Mass Index (BMI) and low academic performance in children 1,2 .…”
Section: Introductionmentioning
confidence: 99%